Welding Process of CFRP and Metal: A Systematic Review - Xinchen QU; Hongjun LI (Engineering Transactions, 2020)
Recently, the applications of carbon fiber reinforced polymer (CFRP) in marine, automobile, aerospace, and other industries have increased significantly. Due to great physical and chemical differences between CFRP and metal, it is not easy to join them together, and this is one of the key problems that many industries need to solve. Thus, a systematic review of the achievements in joining CFRP and metal by welding process is presented in this study to understand the joining mechanism of these materials. Different types of joining methods, such as supersonic welding, laser welding, friction welding, composite welding, and other techniques are studied. The research shows that all different welding methods have pros and cons, and the usage of hybrid joining will be the future trend to improve the joint performance with respect to the joining application of CFRP and metal. In the time ahead, these methods can provide some references for the development of technologies used in joining CFRP and metal.